PENGARUH KUALITAS PRODUK, BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ROTI PADA UD. ROTI TIDAR WADUNGAN-NGASEM-KEDIRI - Dwi Puji Astutik; Djunaidi Djunaidi; Budi Rahayu (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the effect of product quality, brand image, and service quality on bread purchasing decisions at UD. Roti Tidar Kwadungan-Ngasem-Kediri. This research used a quantitative approach with primary data collected from 100 consumers. The sampling technique used accidental sampling. Data were collected through questionnaires, interviews, observation, and documentation. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results show that product quality has a significant effect on purchasing decisions with a significance value of 0.001. Service quality has a significant effect on purchasing decisions with a significance value of 0.010. Brand image also has a significant effect on purchasing decisions with a significance value of 0.023. Simultaneously, product quality, service quality, and brand image significantly affect purchasing decisions with a significance value of 0.000. The Adjusted R Square value of 0.479 indicates that 47.9% of the variation in purchasing decisions can be explained by the three independent variables. These findings indicate that UD. Roti Tidar should maintain product quality, improve service quality, and strengthen brand image to encourage consumer purchasing decisions.